Implementasi CSR terhadap Kesejahteraan Hidup Masyarakat - Andi Mapisangka (Universitas Negeri Malang, 2009)
Corporate Social Responsibility (CSR) is the firm commitment to the environment in achieving social live welfare. This research aims to analyze the effect of CSR of PT. Batamindo Investment Cakrawala to social live welfare. The indicators of CSR are corporate social responsibility goal, corporate social issues, and corporate relation program. The indicators of welfare live are progress on health, education, and economic activity. Based on ordinary least square, this research concludes: corporate social responsibility goal, corporate social issue, and corporate relation program PT. BIC have a positive effect on social live welfare at Batamindo Industrial Area.Based on the findings, the policy of corporate social responsibility by PT. Batamindo Investment Cakrawala should be focused on local social values. This approach is very important in order the CSR program by firm can effectively and efficiently functioning. Besides that, the CSR program must involve all people in company environment, so they will take advantage form the CSR program.Keywords : corporate social responsibility goal, corporate social issue, corporate relation program, ordinary least square, social live welfare__________________________________________________________________________________________